2013
DOI: 10.1111/ijs.12149
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Psychological Factors on Health-Related Quality of Life after Stroke: A Systematic Review

Abstract: There is still a paucity of studies on psychological determinants of poststroke health-related quality of life. The reviewed studies supported the importance of psychological factors, but further research is needed to supplement the available evidence and to examine how psychological factors can be modified to improve health-related quality of life, and at what moment after the stroke these interventions should be given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
72
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 34 publications
1
72
0
1
Order By: Relevance
“…actively addressing the problem) and emotion-focused (e.g. accepting situations more easily) coping styles [7]. Studies have found that problem-focused and emotion-focused coping also become more closely related to health-related quality of life (HRQoL) as more time elapses after a stroke, as the relationship with HRQoL was stronger at one year than at two months post stroke [32].…”
Section: Association Between Illness Cognitions and Life Satisfactionmentioning
confidence: 99%
See 2 more Smart Citations
“…actively addressing the problem) and emotion-focused (e.g. accepting situations more easily) coping styles [7]. Studies have found that problem-focused and emotion-focused coping also become more closely related to health-related quality of life (HRQoL) as more time elapses after a stroke, as the relationship with HRQoL was stronger at one year than at two months post stroke [32].…”
Section: Association Between Illness Cognitions and Life Satisfactionmentioning
confidence: 99%
“…This is in accordance with what was found in the present study. Physical factors may play a more prominent role in life satisfaction in the acute and subacute phases post stroke, whereas psychological factors such as illness cognitions may become more important in the chronic phase [7].…”
Section: Association Between Illness Cognitions and Life Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation
“…Personality problems, including increased neuroticism, are moderately related to lower assessment of HRQL perspectives, whereas coping, internal locus of control, sense of self-worth, hope, and optimism are moderately positively correlated with HRQL, and extrovertedness does not have a relationship with HRQL (Van Mierlo et al, 2014). Undoubtedly, the ability to cope in difficult situations, such as everyday functioning with the consequences of stroke, and the ability to positively solve problems are associated with higher quality of life, which was proved by the Dutch team of researchers led by Visser (Visser et al, 2015).…”
Section: Quality Of Life Post-stroke and Its Determinantsmentioning
confidence: 91%
“…Psychosocial outcomes such as depression, anxiety, employment and driving are impaired after stroke contributing to post stroke disability [1,2]. These outcomes are especially important to investigate in the working age group [3][4][5][6] where younger stroke survivors live longer than older stroke survivors [7].…”
Section: Introductionmentioning
confidence: 99%